2018
DOI: 10.3390/molecules23102553
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effect of Flavonoid Aglycones on the Metabolic Activity of CYP3A4 Enzyme

Abstract: Flavonoids are natural compounds that have been extensively studied due to their positive effects on human health. There are over 4000 flavonoids found in higher plants and their beneficial effects have been shown in vitro as well as in vivo. However, data on their pharmacokinetics and influence on metabolic enzymes is scarce. The aim of this study was to focus on possible interactions between the 30 most commonly encountered flavonoid aglycones on the metabolic activity of CYP3A4 enzyme. 6β-hydroxylation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 58 publications
(76 reference statements)
1
28
0
Order By: Relevance
“…In the previously published screening study, it was shown that acacetin, apigenin, chrysin, and pinocembrin inhibit human cytochrome P450 3A4 at 1 µM concentration. [11] Herein, we have characterized the inhibition kinetics and determined IC50 values inhibition constants (KI), and rates of inhibition (kinact) for each of the aforementioned flavonoids. The strongest inhibitor was chrysin (IC50 0.6 µM, inhibition constant 0.6 µM, inhibition rate constant 0.065 min -1 , inhibition efficacy 0.108 min -1 µM -1 ).…”
Section: Results and Discusionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the previously published screening study, it was shown that acacetin, apigenin, chrysin, and pinocembrin inhibit human cytochrome P450 3A4 at 1 µM concentration. [11] Herein, we have characterized the inhibition kinetics and determined IC50 values inhibition constants (KI), and rates of inhibition (kinact) for each of the aforementioned flavonoids. The strongest inhibitor was chrysin (IC50 0.6 µM, inhibition constant 0.6 µM, inhibition rate constant 0.065 min -1 , inhibition efficacy 0.108 min -1 µM -1 ).…”
Section: Results and Discusionmentioning
confidence: 99%
“…[1,10] In the previously published screening study, it has been shown that acacetin, apigenin, chrysin and pinocembrin are the most prominent inhibitors of human cytochrome P450 3A4 at 1 µM concentration. [11] Flavanone pinocembrin ( Figure 1.) reduces the enzyme activity by 50 %, while flavones acacetin, apigenin and chrysin reduce the enzyme activity to 5 %, 24 % and 17 %, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all identified compounds in HSYW, many flavonoids, such as hesperidin, formononetin and tangeretin, as well as naringin and its deglycosylated metabolite naringenin, were found to be reversible inhibitors of a panel of human CYPs, such as CYP1A, CYP2A6 and CYP3A. [ 39–46 ] Meanwhile, some major constituents in liquorice (the root of G. ularensis ) and the root of Radix Astragali , such as glycyrrhetinic acid, licochalcone A, astragaloside IV and caffeic acid, have also been found with strong inhibition on CYP3A. [ 34,47–50 ] These constituents in HSYW may be the contributors for CYP inhibition, and thereby to play crucial roles in modulating the pharmacokinetic behaviour of apatinib via inhibition on human CYPs.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the activity of CYP450 enzymes is one of the reasons for interactions between supplements and drugs that may cause adverse events. Therefore, effects of PPL and its major ingredients on CYP450 activities has been characterized recently [13][14][15][16]. For instance, Naramoto et al has reported that ethanol extraction of Brazilian Green PPL inhibited enzymatic activities of all the tested CYP enzymes (CYP1A2, 2C9, 2C19, 2D6, and 3A4) in vitro in a concentration-dependent manner [13].…”
Section: Introductionmentioning
confidence: 99%